Anthropogenic tritium: Inventory, discharge, environmental behavior and health effects. (January 2021) - Nie, Baojie; Fang, Sheng; Jiang, Man; Wang, Laishun; Ni, Muyi; Zheng, Jiye; Yang, Zhiyi; Li, Fengchen
Abstract: As a special and dominant radionuclide released from the nuclear industry, tritium is a "superstar" radionuclide receiving significant concerns from the scientific community, regulators and even the public. This characteristic gradually becomes more and more prominent along with the rapid development of fusion energy research in particular and operations of fission nuclear reactors as well. Various aspects of tritium studies including, but not limited to, the tritium resource, fusion tritium technology (such as extraction, separation and fueling), tritium management and discharge, tritium environmental behavior, radiation dose and health effects have been and are being conducted. The objectives of this study are as follows: (1) to detail the tritium production, inventory and discharge of nuclear facilities from the perspectives of both practices and regulatory requirements, (2) to illustrate tritium environmental behavior & modeling in both the terrestrial and aquatic systems, in which an air-water transfer behavior (deposition and evaporation) was specifically explained, (3) to identify and discuss the radiation dose to a person under normal and accidental tritium discharges, (4) to review the health effects and risks in relation to tritium exposure. The main contribution is to comprehensively recognize the anthropogenic tritium from its generation to the possible damage to human health. It is expected to be instrumental for the beginners in the related fields and attract more scholars' attention to the tritium safety issue when performing directly or related studies so as to ensure the safe operation of nuclear systems, in particular the future fusion energy system. Highlights: Development of nuclear energy involving fusion was reviewed. Tritium production, inventory and discharge of nuclear facilities were detailed. Tritium environmental behavior and modeling were illustrated. Public radiation dose in relation to tritium release was identified and discussed. Health effects and risks in relation to tritium exposure were reviewed.